Keberagaman Gender Dan Pelaporan Keberlanjutan: Kajian Literatur Atas Pengaruh Di Tingkat Direksi - I Wayan Adnyana; I Putu Andika Pratama; Ni Wayan Lady Andini; Ni Putu Nita Sri Natih (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This research aims to explore the relationship between gender diversity on boards of directors and corporate sustainability performance through a literature review analysis. The research methodology employs a literature review approach by examining 11 relevant articles related to the impact of gender diversity on sustainability report disclosure, using inclusion criteria such as article type, methodology, and topic relevance. The analysis results show diverse findings, with most articles stating that gender diversity has a positive impact on sustainability reporting, especially in industrial sectors with high exposure to social and environmental issues. However, some studies also found no significant impact, especially in regions with a strong patriarchal culture, such as Indonesia. The conclusion of this study emphasizes the importance of increasing women's representation in corporate governance to maximize sustainability performance and more transparent disclosures.